2015
DOI: 10.1080/2162402x.2015.1049805
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tumor cells with infiltrating lymphocytes via CD70 and CD27 in clear cell renal cell carcinoma

Abstract: CD70 upregulation by hypoxia-inducible factor and CD27 lymphocyte tumor infiltration are associated with worse survival in von Hippel-Lindau gene mutated clear cell renal cell carcinoma (ccRCC). CD70/CD27 interaction is accompanied by high soluble CD27 levels in the sera of ccRCC patients suggesting that soluble CD27 is a potential predictive tool for anti-CD70 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In addition, the interferon-inducible CXCR3 ligands score based on expression levels of CXCL9 , CXCL10 and CXCL11, is suggested to be linked with different risk subgroups of recurrence and mortality in patients with ccRCC ( 42 ). CD27 + lymphocyte infiltration and the overexpression of CD70 are correlated with poor prognosis in ccRCC, and an elevated serum level of CD27 may be used for anti-CD70 therapy by predicting CD70-expressing ccRCC ( 43 , 44 ). RUNX3 is closely associated with RCC progression, and its high expression can significantly suppress the migration, invasion and angiogenesis in RCC ( 45 - 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interferon-inducible CXCR3 ligands score based on expression levels of CXCL9 , CXCL10 and CXCL11, is suggested to be linked with different risk subgroups of recurrence and mortality in patients with ccRCC ( 42 ). CD27 + lymphocyte infiltration and the overexpression of CD70 are correlated with poor prognosis in ccRCC, and an elevated serum level of CD27 may be used for anti-CD70 therapy by predicting CD70-expressing ccRCC ( 43 , 44 ). RUNX3 is closely associated with RCC progression, and its high expression can significantly suppress the migration, invasion and angiogenesis in RCC ( 45 - 47 ).…”
Section: Discussionmentioning
confidence: 99%
“… 45 Other studies have shown that Granzyme A (GZMA) is related to the efficacy of ICIs in many cancer types. 46 , 47 TNF-α is an effective inflammatory cytokine mainly produced by activated macrophages, lymphocytes, and other cell types. TNF-α plays an important role in inflammatory immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The following immunostimulatory antibodies that do not operate as checkpoint blockers are also being evaluated for their safety and efficacy when administered in combination with EBRT: (1) the FDA-approved mAb adalimumab, an inhibitor of TNF and hence of immunosuppressive TAMs, [189][190][191][192][193] which is tested together with EBRT in patients with anaplastic thyroid tumors (NCT02516774); (2) fresolimumab, a mAb that neutralizes TGFb1, 22,66,[194][195][196][197] which is studied in combination with EBRT in individuals with NSCLC (NCT02581787); and (3) varlilumab, an immunostimulatory mAb specific for CD27, [198][199][200][201] which is assessed for its capacity to improve the efficacy of EBRT in subjects with prostate carcinoma (NCT02284971) ( Table 1).…”
Section: E1214790-4mentioning
confidence: 99%